Non-invasive Monitoring of Brain Temperature during Rapid Selective Brain Cooling by Zero-Heat-Flux Thermometry - Bakhsheshi, Mohammad Fazel; Ho, Marjorie; Keenliside, Lynn; Lee, Ting-Yim (Emerging Science Journal, 2019)
Introduction: Selective brain cooling can minimize systemic complications associated with whole body cooling but maximize neuroprotection. Recently, we developed a non-invasive, portable and inexpensive system for selectively cooling the brain rapidly and demonstrated its safety and efficacy in porcine models. However, the widespread application of this technique in the clinical setting requires a reliable, non-invasive and accurate method for measuring local brain temperature so that cooling and rewarming rates can be controlled during targeted temperature management. In this study, we evaluate the ability of a zero-heat-flux SpotOn sensor, mounted on three different locations, to measure brain temperature during selective brain cooling in a pig model. Computed Tomography (CT) was used to determine the position of the SpotOn patches relative to the brain at different placement locations.Methods and Results: Experiments were conducted on two juvenile pigs. Body temperature was measured using a rectal temperature probe while brain temperature with an intraparenchymal thermocouple probe. A SpotOn patch was taped to the pig’s head at three different locations: 1-2 cm posterior (Location #1, n=1), central forehead (Location #2, n=1); and 1-2 cm anterior and lateral to the bregma i.e., above the eye on the forehead (Location #3, n=1). This cooling system was able to rapidly cool the brain temperature to 33.7 ± 0.2°C within 15 minutes, and maintain the brain temperature within 33-34°C for 4-6 hours before slowly rewarming to 34.8 ± 1.1°C from 33.7 ± 0.2°C, while maintaining the core body temperature (as per rectal temperature probe) above 36°C. We measured a mean bias of -1.1°C, -0.2°C and 0.7°C during rapid cooling in induction phase, maintenance and rewarming phase, respectively. Amongst the three locations, location #2 had the highest correlation (R2 = 0.8) between the SpotOn sensor and the thermocouple probe.Conclusions: This SBC method is able to tightly control the rewarming rate within 0.52 ± 0.20°C/h. The SpotOn sensor placed on the center of the forehead provides a good measurement of brain temperature in comparison to the invasive needle probe.